Sistem Pendukung Keputusan Pemilihan Atlet Panahan Menggunakan Metode Analitycal Hierarchy Process Berbasis Web - Bimantara, Eka Bayu; Budiman, Arief; Utomo, Pradityo (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2018)
Decision Support System is a system was used to help getting making decisions on a problem, such as selecting students in the archery sports that will be face to a championship event such as SEA GAMES (South East Games). In Decision Support System there are many methods that can be used, one of them is Analitycal Hierarchy Process method. Analitycal Hierarchy Process method is one of the more efficient decision-making methods because the data is very detailed, all the criteria and alternatives will be compared one by one. The calculation used to solve a problem uses multiplication to relate the preference value, where the value for each criteria and alternative must be searched for eigen / priority vector first, after it is proved consistency using RI table (ratio index), if the result of verification is less than 10% (0.1) then it is consistent and the calculation can be continued, but if the verification result is more than 10% (0.1) then the calculation is considered inconsistent and needs to be repeated from the beginning. This support system uses a web base, where the data entered will be saved into the MySQL database. The test results of the Student Selection Selection Decision Support System Using Analitycal Hierarchy Process Method Based Web get results as expected on the Black Box. So it can be concluded an accurate percentage of system success of 100%.Keywords : Decision Support System, Black Box, Analitycal Hierarchy Process, The Selection Of Athlete.